2021
DOI: 10.17239/l1esll-2021.21.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating figurative language from literary texts: second-language instruction as a dual literacy practice

Abstract: The aim of this article is to contribute knowledge about how figurative language from literary texts is negotiated through oral interaction in second-language instruction. The material consists of transcriptions of recordings from a classroom study of basic adult second-language instruction involving two teachers and their two student groups. Theories of semantic waves and discursive mobility are used to explore and visualize discursive shifts between concrete and condensed abstract meanings. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…This variable describes activities in specific areas of lived experience, such as seafaring, and the people and things involved in these activities. A more general feature of literary texts is the use of literary descriptions, involving metaphors and expanded noun groups ( Martin & Rose, 2008 ;Walldén & Nygård Larsson, 2021a ). One example from the book used in the study is "the most exclusive districts of Istanbul".…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…This variable describes activities in specific areas of lived experience, such as seafaring, and the people and things involved in these activities. A more general feature of literary texts is the use of literary descriptions, involving metaphors and expanded noun groups ( Martin & Rose, 2008 ;Walldén & Nygård Larsson, 2021a ). One example from the book used in the study is "the most exclusive districts of Istanbul".…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…One of the changes in a recently implemented revision of the national curriculum specific for Swedish as a second language 1 (SSL) ( Skolverket, 2022 ) is that the teaching should focus on the "words and expressions" of literary texts. The wording is not present in the corresponding curriculum from subject Swedish, which indicates the extra linguistic support expected in teaching the majority language from a second-language perspective ( Hedman & Magnusson, 2020 ;Walldén & Nygård Larsson, 2021a ). While this seems to align with a literacy paradigm in language arts education ( Gourvennec et al, 2020 ), there is nothing in the curriculum indicating either the nature of these words and expressions or how they should be highlighted in teaching practice to support engagement with literary texts in linguistically diverse classrooms.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…In such classrooms, it is important to consider how the negotiation of linguistic hurdles plays a part in the re-appropriation of old books. Robert Walldén (2020;Walldén & Nygård Larsson, 2021), in his study of adult second language education, highlighted how the social practice of reading a novel in the target language revolved to a considerable extent around the need to understand words and expressions in the book. In contrast to the frequently expressed concerns that literature has been reduced to a vehicle for language development (e.g., Carroli, 2008), the study found that the teachers' explanations of the literary language seemed central to the students' making meaning of the book.…”
mentioning
confidence: 99%